The Influence of Job Descriptions and Job Spesifications on the Performance of Makassar City Regional Drinking Water Company Employees - Wiras Vantika; M. Yusuf Alfian Rendra Anggoro; Arniati, Arniati (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the effect of job descriptions and job specifications on the performance of Makassar City Drinking Water Company employees. The type of research used in this research is quantitative. The sample used in this research was 77 respondents. The data collection technique uses a questionnaire technique. The data analysis technique used to test the hypothesis is multiple linear regression and the t test (partial test) which is processed using statistical calculations via the Statistical Package for the Social Science (SPSS) version 26. The results of the study show that Job Descriptions have a positive and significant effect on Employee Performance at the Makassar City Regional Drinking Water Company as evidenced by the Job Description regression coefficient (X1) of 0.453 and a calculated t value of 8.993 > t table 1.665 with a significance value of 0.000 < 0.05. And Job Specifications have a positive and significant effect on the Performance of Employees of the Regional Drinking Water Company of Makassar City as evidenced by the Job Specifications regression coefficient (X2) of 0.261 and a calculated t value of 2.763 > t table 1.665 with a significance value of 0.007 <0.05.